Comparative Analysis of the Efficiency of Islamic and Conventional Banking Systems: A literature review - Anton Priyo Nugroho (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The article aims to conduct an Efficiency Comparison between Islamic and Conventional Banking Systems by synthesizing a literature review within the realm of Financial Management. Employing a literature study methodology, the author meticulously examines prior research findings to construct a robust conceptual framework. This approach comprehensively outlines the pertinent theoretical landscape, elucidates recent advancements, and establishes a robust foundation for discourse, drawing from contemporary references accessed through Google Scholars and Mendeley citation searches.Through the analysis of previous studies, the article references significant disparities in the efficiency systems of Islamic banks and conventional banks across their distinct features, each presenting unique advantages. This underscores the need for further analysis of components like sharia compliance, capital structure, and social values, which play pivotal roles in enhancing the efficiency of Islamic banking.